Effect of Cyclotriphosphazene-Based Curing Agents on the Flame Resistance of Epoxy Resins - Zarybnicka, Lucie; Machotova, Jana; Kopecka, Radka; Sevcik, Radek; Hudakova, Martina; Pokorny, Jaroslav; Sal, Jiri (Polymers, 2020)
Epoxy resins are characterized by excellent properties such as chemical resistance, shape stability, hardness and heat resistance, but they present low flame resistance. In this work, the synthesized derivatives, namely hexacyclohexylamino-cyclotriphosphazene (HCACTP) and novel diaminotetracyclohexylamino-cyclotriphosphazene (DTCATP), were applied as curing agents for halogen-free flame retarding epoxy materials. The thermal properties and combustion behavior of the cured epoxy resins were investigated. The obtained results revealed that the application of both derivatives significantly increased flame resistance. The epoxy resins cured with HCACTP and DTCATP exhibited lower total heat release together with lower total smoke production compared to the epoxy materials based on conventional curing agents (dipropylenetriamine and ethylenediamine). Comparing both derivatives, the HCACTP-cured epoxy resin was found to provide a higher flame resistance. The designed novel class of epoxy materials may be used for the preparation of materials with improved flame resistance properties in terms of flame spreading and smoke inhibition.
Keywords: thermal degradation; synthesis; cyclotriphosphazene derivative; epoxy resin; cone calorimeter; curing agent; flame resistance